2011
DOI: 10.1007/s11069-011-9731-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the flood vulnerability of deltaic Kuching City, Malaysia

Abstract: The main objective of this writing is to present a practical way to envisage the flood vulnerability in deltaic region, particularly on the concern of sea level rise. Kuching city of Malaysia is established on banks of Sarawak River, 30 km from the sea. Therefore, it is subjected to fluvial and tidal floods. Kuching Bay experiences the highest King Tides in Southeast Asia region. These tide magnitudes could be a glimpse of future sea level rise. By means of modelling these tides, it provides an understanding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Other research has evaluated the impacts of SLR in coastal and estuarine zones. For example, Mah et al [6] analyzed the effects of SLR on the city of Kuching (1 • N, Malaysia), located 30 km from the coast in the Saeawak River delta, at an altitude of 5 m. They concluded that a 10% tidal increase would result in a 6% increase in flooded surface area, compared to current levels. The tidal magnitudes in this area are much higher than those recorded in the Andalién River, reaching an average sea level of +4.5 m, which can be seen in the tidal influence up to 30 km upriver from the mouth of the Sarawak River.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has evaluated the impacts of SLR in coastal and estuarine zones. For example, Mah et al [6] analyzed the effects of SLR on the city of Kuching (1 • N, Malaysia), located 30 km from the coast in the Saeawak River delta, at an altitude of 5 m. They concluded that a 10% tidal increase would result in a 6% increase in flooded surface area, compared to current levels. The tidal magnitudes in this area are much higher than those recorded in the Andalién River, reaching an average sea level of +4.5 m, which can be seen in the tidal influence up to 30 km upriver from the mouth of the Sarawak River.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, coastal floods have become a serious problem on a global scale [2,3]. Close to 50% of the global population is concentrated in coastal areas, which are densely populated and economically attractive [4][5][6]. In the 20th century, the frequency of floods and the magnitude of damages increased [7], and a significant further increase in flooding risk is expected in the 21st century, according to models of average sea level rise (ASLR) due to global climate change (GCC), land-use changes driven by global socioeconomic growth [4,[8][9][10][11], and population growth [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ground elevation thus results in these points to obtain flood depths and its associated extents [7]- [8]. It would come out a basin-wide flood map in conjunction to the anticipated flood event.…”
mentioning
confidence: 99%
“…METHOD A 1-D hydrodynamic model -InfoWorks River Simulation (RS) is utilized for modelling the hydraulics of Sarawak River systems. Examples of such modelling are reported by Mah et al[11]. What river modelling means in practical terms is that software incorporates the fundamental laws of moving water bodies along an open channel (in this case, St. Venant Equations) into a simulated environment where flows and water levels change over time.…”
mentioning
confidence: 99%